Effectiveness Of Massage Therapy On Fatigue In Cancer Patients Undergoing Chemotherapy: Scoping Review - Indraswati, Ita; Septiyan, Raditya Bagus; Matchaya, Pasikorn; Finch, Rosie (Universitas Muhammadiyah Surakarta, 2024)
Cancer patients undergoing chemotherapy have side effects. Side effects felt by cancer patients undergoing chemotherapy include nausea and vomiting, diarrhea, constipation, bone marrow damage, peripheral neuropathy, alopecia, pain and fatigue. Fatigue is a condition that occurs in patients because the bone marrow stops producing red blood cells during the chemotherapy process. Fatigue can be severe when patients experience pain, depression and lack of sleep. Fatigue management can be done with non-pharmacological therapy, one of the therapy is massage therapy. Massage therapy can be a manual stimulation of tissues in the body to improve blood circulation, relax muscles, reduce pain and fatigue, and improve sleep quality. Massage therapy can overcome anxiety and reduce fatigue significantly. This study aims to determine the effect of massage therapy on fatigue in cancer patients undergoing chemotherapy. The researchers used several databases such as Pubmed and Science direct. A total of 9 articles were analyzed. In the article there are several massage therapy interventions used to overcome fatigue in cancer patients including accupressure, reflexology, thai massage, back massage, progressive muscle relaxation. Based on several journals that have been analyzed, it can be concluded that the provision of massage therapy interventions can reduce the level of fatigue in cancer patients.